2012
DOI: 10.2174/138920012803341366
|View full text |Cite
|
Sign up to set email alerts
|

Is the Autophagy Induced by Thiopurines Beneficial or Deleterious?

Abstract: Thiopurines (azathioprine, 6-mercaptopurine and 6-thioguanine), are drugs useful in the treatment of leukemia, autoimmune diseases, as well as in organ transplantation. After many years of use is still not well understood their mode of action. Recently, several groups have found that thiopurines can activate autophagy by different mechanisms. Autophagy is a process of auto-digestion. After an infection, radiation, injury, oxidative stress, or after drug treatment, the cellular organelles may be damaged. In tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Thiopurines, including azathioprine and 6-mercaptopurine, are immunosuppressant drugs used to maintain remission in patients with IBD[78]. Thiopurines and autophagy have also been shown to be correlated by the adverse effects of treatment.…”
Section: Role Of Autophagy In Ibd Therapy and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiopurines, including azathioprine and 6-mercaptopurine, are immunosuppressant drugs used to maintain remission in patients with IBD[78]. Thiopurines and autophagy have also been shown to be correlated by the adverse effects of treatment.…”
Section: Role Of Autophagy In Ibd Therapy and Future Prospectsmentioning
confidence: 99%
“…It was shown that autophagy might represent an important route for the clearance of TPMT*3A aggregates and/or aggregate precursors[84]. Due to the severe adverse effects of thiopurines, a potential protective role for autophagy in hepatocytes has been investigated; it has been shown that autophagy has a protective role in hepatocytes during thiopurine therapy[78]. …”
Section: Role Of Autophagy In Ibd Therapy and Future Prospectsmentioning
confidence: 99%
“…Silencing of ULK1 , Atg5 or Atg7 contributes to increased apoptosis in response to CsA, further supporting a protective role of autophagy following CsA treatment 91 . Similar to CsA, thiopurine can activate autophagy and also appears to serve as a compensatory protective mechanism to counter cytotoxicity 92 . Thus, the strategic use of immunosuppressants that also promote autophagy might serve to decrease the intrinsic cytotoxic effects of these agents.…”
Section: Modulating Autophagy In Clinical Transplantationmentioning
confidence: 87%
“…73 They have a relatively slow onset but can maintain remission in moderate to severe cases of CD and have also shown some effectiveness for the induction of remission. 3,74 The commonly used pro-drug azathioprine is converted to 6-mercaptopurine [6-MP] by glutathione in the intestinal wall.…”
Section: Autophagy and Crohn’s Diseasementioning
confidence: 99%
“…Autophagy is activated in hepatocytes treated with thiopurines, possibly as a secondary response to the hepatotoxic effects of the drug [Figure 3]; however, it could also indicate that autophagy is directly modulated to balance immune responses in patients. 73,78 Despite the lack of understanding of the mechanism of action of thiopurines, it has been shown that autophagy has a protective role in hepatocytes during thiopurine therapy, 73 suggesting that a combination treatment of thiopurines with drugs that induce autophagy may reduce their adverse effects, enhancing their efficacy and safety.…”
Section: Autophagy and Crohn’s Diseasementioning
confidence: 99%